Association Between Healthy Eating Index-2015 and Kidney Stones in American Adults: A Cross-Sectional Analysis of NHANES 2007–2018 - Yin, Shan; Wang, Jiahao; Bai, Yunjin; Yang, Zhenzhen; Cui, Jianwei; Xiao, Yunfei; Wang, Jia (Frontiers in Nutrition, 2022)
Purpose: To explore the association between Healthy Eating Index (HEI)-2015 and kidney stones in an American adult population. Materials and Methods: National Health and Nutrition Examination Survey (NHANES) datasets from 2007 to 2018 were used. Participants aged ≥ 20 years who reported kidney stone history and sleep duration were included. Weighted proportions, multivariable analysis and spline smoothing were used to evaluate the associations between HEI-2015 and nephrolithiasis by adjusting gender, age, race, poverty income ratio, body mass index, education level, marital status, smoking, alcohol intake, energy level, vigorous activity, moderate activity, and some comorbidities. Results: Totally 30 368 American adults were included, with weighted mean age (standard deviation (SD)) of 47.69 (16.85) years. The overall mean HEI-2015 score (SD) was 50.82 (13.80). In the fully-adjusted multivariable model, HEI-2015 was negatively correlated with urolithiasis (odds ratio (OR) = 0.991; 95% confidence interval (CI) 0.988 to 0.994). Compared with the first quartile of HEI- 2015, the population in the fourth quartile of HEI-2015 had a lower prevalence of kidney stones (OR = 0.716; 95% CI 0.635 to 0.807). The association was modified by education and vigorous activity. Conclusions: HEI-2015 is inversely associated with the prevalence of kidney stones, which means better diet quality is associated with a lower risk of nephrolithiasis.